Beyond the Comfort Zone: Strengthening Mindset and Mental Health Among Family Beneficiary Assistants (KPM Facilitators) - Yudi Suharsono; Tulus Winarsunu; Diah Karmiyati; Jabal Tarik Ibrahim (Jurnal Locus Penelitian dan Pengabdian, 2026)
Family Beneficiary Assistants (Keluarga Penerima Manfaat/KPM facilitators) work under high-pressure conditions that may trigger defensive behaviors, or safety behaviors, and increase the risk of burnout. This community service activity aimed to examine the effectiveness of an intervention based on a mental health-informed approach in improving the psychological readiness of facilitators. The program was carried out over one month and involved 150 KPM facilitators in Kediri Regency using a pretest-posttest design and a mixed-methods approach. The results of this community service activity showed significant increases in cognitive awareness (+17.9%), growth mindset (+18.1%), and self-efficacy (+16.4%), accompanied by a decrease in safety behavior (-18.2%). In addition, emotional well-being increased by 9%. The qualitative findings indicated a shift from a survival-oriented state to a more empowered state, characterized by an increased sense of psychological safety and professional courage.